Significações do trabalho publicitário: as representações da atividade nos discursos autorreferenciais do Anuário do Clube de Criação de São Paulo - Gonçalves, Heraldo Bighetti (2011)
The world of advertising work is analyzed from the graphic designs and manifests that characterize the Yearbook of the Club of Creation of São Paulo. The publication, that to each year is proposed to give visibility to the best of Brazilian advertising, according to the advertisement professionals, is support for speeches that represent the professional activity, conceived as creative manifestations that seek to extend the significances in the production sphere. In this way, the world of the advertising work, conceived as a commodity for a symbolic consumption, amplifies and enhances the connotations of the immateriality of its production, dialoguing with the most diverse spheres of culture to reorganize it, to edit the world due to its presence. The labor issue is addressed in its social and cultural aspects, to organize the theoretical background and the analysis of the corpus of research.